Technical note: A comparative study of chemistry schemes for volcanic sulfur dioxide in Lagrangian transport simulations – a case study of the 2019 Raikoke eruption - M. Liu; M. Liu; L. Hoffmann; L. Hoffmann; J.-U. Grooß; J.-U. Grooß; Z. Cai; S. Grießbach; S. Grießbach; Y. Heng (Atmospheric Chemistry and Physics)
Lagrangian transport models are important tools to study the sources, spread, and lifetime of air pollutants. In order to simulate the transport of reactive atmospheric pollutants, the implementation of efficient chemistry and mixing schemes is necessary to properly represent the lifetime of chemical species. Based on a case study simulating the long-range transport of volcanic sulfur dioxide (SO2) for the 2019 Raikoke eruption, this study compares two chemistry schemes implemented in the Massive-Parallel Trajectory Calculations (MPTRAC) Lagrangian transport model. The explicit scheme represents first-order and pseudo-first-order loss processes of SO2 based on prescribed reaction rates and climatological oxidant fields, i.e., the hydroxyl radical in the gas phase and hydrogen peroxide in the aqueous phase. Furthermore, an implicit scheme with a reduced chemistry mechanism for volcanic SO2 decomposition has been implemented, targeting the upper-troposphere–lower-stratosphere (UT–LS) region. Considering nonlinear effects of the volcanic SO2 chemistry in the UT–LS region, we found that the implicit solution yields a better representation of the volcanic SO2 lifetime, while the first-order explicit solution has better computational efficiency. By analyzing the dependence between the oxidants and SO2 concentrations, correction formulas are derived to adjust the oxidant fields used in the explicit solution, leading to a good trade-off between computational efficiency and accuracy. We consider this work to be an important step forward to support future research on emission source reconstruction involving nonlinear chemical processes.